Benefits from energy policy synchronisation of Brazil's North-Northeast interconnection. (December 2020) - Herrera, Milton M.; Dyner, Isaac; Cosenz, Federico
Abstract: During the last 10 years Brazil has accelerated the incorporation of new wind capacity into its power matrix. This situation has generated the need for increased transport capacity. However, there have been delays in the planning process for new transmission line construction, thus inducing trapped electricity in the system; in other words, electricity that cannot be dispatched to the interconnected system. Using system dynamics modelling, this paper assesses energy policy alternatives for improving the synchronisation between the construction of both power generation and transmission capacities. Simulation results show that policy synchronisation within the wind industry may provide important opportunities regarding security of supply. This paper concludes that in Brazil's case it is possible to attain a balance between wind power expansion and interconnection capacity through synchronised and systemic interventions. Highlights: Power systems require a sustainable balance between supply and demand. Wind power industry could be affected by energy policy fragmentation. This article assesses alternative policy options to contribute to the existing literature on grid congestion. New insights on the synchronisation of energy policies for the wind industry expansion is offered.